2023
DOI: 10.1161/circgen.122.003710
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Gene-Smoking Interaction Analysis in Relation to Subclinical Atherosclerosis-Results From the IMPROVE Study

Abstract: Background: Smoking is associated with carotid intima-media thickness (C-IMT). However, knowledge about how genetics may influence this association is limited. We aimed to perform nonhypothesis driven gene-smoking interaction analyses to identify potential genetic variants, among those included in immune and metabolic platforms, that may modify the effect of smoking on carotid intima-media thickness. Materials: We used baseline data from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…Smoking can promote the progression of systemic inflammation and promote the occurrence and development of atherosclerosis (Doran et al, 2003;Chang et al, 2014;Papagoras et al, 2014;Gulati et al, 2016;Rodríguez Huerta et al, 2016). Buamina et al found that there was an interaction between smoking and genes that may promote the development of carotid atherosclerosis (Maitusong et al, 2023). Reducing tobacco inhalation can reduce the incidence of carotid atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Smoking can promote the progression of systemic inflammation and promote the occurrence and development of atherosclerosis (Doran et al, 2003;Chang et al, 2014;Papagoras et al, 2014;Gulati et al, 2016;Rodríguez Huerta et al, 2016). Buamina et al found that there was an interaction between smoking and genes that may promote the development of carotid atherosclerosis (Maitusong et al, 2023). Reducing tobacco inhalation can reduce the incidence of carotid atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Buamina et al. found that there was an interaction between smoking and genes that may promote the development of carotid atherosclerosis (Maitusong et al., 2023 ). Reducing tobacco inhalation can reduce the incidence of carotid atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a study found that the combination of certain genetic variants and high blood pressure was associated with an increased risk of HE in ICH patients ( 30 ). Another study found that the interaction between genetic variants and smoking was associated with an increased risk of HE and poor outcomes in ICH patients ( 31 ).…”
Section: Etiologymentioning
confidence: 99%